2011
DOI: 10.1089/scd.2010.0084
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein 4 Mediates Human Embryonic Germ Cell Derivation

Abstract: Human primordial germ cells (PGCs) have proven to be a source of pluripotent stem cells called embryonic germ cells (EGCs). Unlike embryonic stem cells, virtually little is known regarding the factors that regulate EGC survival and maintenance. In mice, the growth factor bone morphogenetic protein 4 (BMP4) has been shown to be required for maintaining mouse embryonic stem cells, and disruptions in this gene lead to defects in mouse PGC specification. Here, we sought to determine whether recombinant human BMP4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…In agreement with mouse, transmembrane SCF expression of the feeder layer promoted human PGC growth (Kerr et al, 2006). It is also possible to derive and maintain human EGCs without serum using 15-20% KSR (Invitrogen) (Turnpenny et al, 2003;Pan et al, 2005;Hua et al, 2009;Hiller et al, 2011). Whereas serum provides essential nutrients also provides some factors that promote differentiation of EGCs and make the analysis of the experiments difficult.…”
Section: Growth Mediummentioning
confidence: 82%
See 4 more Smart Citations
“…In agreement with mouse, transmembrane SCF expression of the feeder layer promoted human PGC growth (Kerr et al, 2006). It is also possible to derive and maintain human EGCs without serum using 15-20% KSR (Invitrogen) (Turnpenny et al, 2003;Pan et al, 2005;Hua et al, 2009;Hiller et al, 2011). Whereas serum provides essential nutrients also provides some factors that promote differentiation of EGCs and make the analysis of the experiments difficult.…”
Section: Growth Mediummentioning
confidence: 82%
“…Recently it has been reported that the addition of 5-20 ng/ml recombinant BMP4 (R&D Systems) increases, in a dose-responsive manner, the efficiency of EGC derivation and maintenance. The results revealed an increase in EGC derivation of 5-fold with 20 ng/ml BMP4 and, after 3 weeks the survival efficiency increased by 50-fold in the presence of BMP4 (Hiller et al, 2011). Survival appeared to be in part related to the ability of BMP4 to inhibit spontaneous differentiation in these cultures, an inherent problem with long-term maintenance of human EGC cultures.…”
Section: Growth Mediummentioning
confidence: 90%
See 3 more Smart Citations